1982
DOI: 10.1055/s-2007-1021569
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma Occurring in a Hyperplastic (Metaplastic) Polyp of the Colon

Abstract: A case of adenocarcinoma occurring in a hyperplastic (metaplastic) polyp of the colon is presented. The polyp, two cm in diameter, was located in the transverse colon of a 45-year-old male patient, and was removed endoscopically. From the periphery to the centre, the polyp showed epithelial changes progressing from hyperplastic to severely dysplastic, terminating in a central focus of invasive adenocarcinoma. It is suggested that the considerable number of absorptive cells in large hyperplastic polyps may occa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The size of the polypectomised specimens did not diVer significantly between serrated adenomas and traditional adenomas, at 12 (6) mm v 13 (3) mm. There were four serrated adenomas which contained areas of high grade dysplasia (figs 2 and 3).…”
Section: Dysplasiamentioning
confidence: 77%
See 2 more Smart Citations
“…The size of the polypectomised specimens did not diVer significantly between serrated adenomas and traditional adenomas, at 12 (6) mm v 13 (3) mm. There were four serrated adenomas which contained areas of high grade dysplasia (figs 2 and 3).…”
Section: Dysplasiamentioning
confidence: 77%
“…The presence of neoplastic change within hyperplastic polyps or in neoplasms mimicking hyperplasia in the general population, [6][7][8][9] in metaplastic polyposis, 15 16 or even in hereditary non-polyposis colorectal cancer 5 has raised the possibility that hyperplastic polyps may be another precursor of human colorectal cancer. The serrated adenoma can be regarded as a specific lesion which might explain the occurrence of neoplasia within hyperplastic polyps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One carcinoma reported in an individual with HPS was shown to have arisen in an otherwise typical tubular adenoma. 16 Furthermore, although cases of adenocarcinoma have been reported as actually arising within sporadic hyperplastic polyps and serrated adenomas, 17,18 to date this phenomenon has not been reported in individuals with the HPS syndrome.…”
mentioning
confidence: 99%
“…On the other hand, larger hyperplastic polyps carry an increased potential for dysplastic change. 1,2 We have shown previously that a mutation of the K-ras gene was detectable in approximately one-half of the hyperplastic polyps we studied. 3 Another study has suggested that hyperplastic polyps may show clonal genetic alterations and microsatellite instability.…”
mentioning
confidence: 91%